Application of Gauss's Law in High Energy Capacitor Design for Electric Vehicles: A Systematic Literature Review - Melly Junita; Hamdi Akhsan; Fitri Nisa (Lambung Mangkurat University Press, 2026)
This article uses a PRISMA flowchart-based Systematic Literature Review (SLR) approach to analyze the role of Gauss's Law in the design of high-energy dielectric capacitors for electric vehicles. Through a synthesis of 17 recent studies (2019–2025), this article identifies three main themes: (1) the application of Gauss's Law in electric field distribution analysis, (2) optimization of dielectric geometry and materials, and (3) the potential application of high-energy capacitors in electric vehicle power systems, especially as high-power components in inverters and regenerative braking. The results show that understanding the field distribution based on Gauss's Law is key to improving the energy density (>18 J/cm³) and operational reliability of capacitors. This study confirms that Gauss's Law is not only a theoretical principle, but a practical engineering foundation for sustainable energy storage technologies.